Influence of Plagiarism Checker Software on Plagiarism Practices among Postgraduate Students in Public Universities in Abia and Imo States - Uzuegbu , C. P.; Tsenongu, C. T. (Communicate: Journal of Library and Information Science, 2024)
This paper examined the influence of adoption of plagiarism software on plagiarism practices of postgraduate students of universities in Abia and Imo states under three specific objectives. Four public universities in Abia and Imo states were investigated (Michael Okpara University of Agriculture Umuidike, Abia State University, Uturu, Federal University of Technology, Owerri, and Imo State University, Owerri). The descriptive survey design was adopted for the study. The population of the study is three thousand, twenty-four (3,024) postgraduate students in public universities in Abia and Imo States. A sample of 341 postgraduate students was drawn using Krejice and Morgan (1970) formula for determination of sample size and further stratified proportionately across the studied institutions. A questionnaire developed by the researchers was used to collect data for the study. Both descriptive and inferential statistics of mean ratings and Pearson Product Moment Correlation (PPMC) coefficient respectively were used to fulfil the objectives of the study. The study indicated that implementation of plagiarism software has a positive impact on plagiarism practices among postgraduate students in universities in Abia and Imo States. The study recommended that universities should collaborate with their librarians to teach postgraduate students academic writing techniques, citation and referencing styles, whilst adopting plagiarism software to curtail plagiarism practices among postgraduate students in their institutions. , , ,